The Relation of Knowledge in Restorative Dentistry in Upper-Middle-Class Society with Frequency of Regular Dental Visits - Sari, Morita; Mawarni, Karisma Aulia (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2022)
The development of education, socioeconomic conditions, technology, and public awareness of the importance of oral and dental health encourages an improvement of dental and oral health services. This service form is a visit to the dentist. Middle to upper-class societies with better economic conditions and good education have a greater opportunity in gaining knowledge about restorative dentistry care as well as in utilizing dental and oral health services. The purpose of the research is to know the relation of restorative dentistry care knowledge with the frequency of regular visits to dentists in upper-middle-class society. Method: using a cross-sectional study design with the instrument of research in questionnaire form. The number of samples was 100 people using the purposive sampling method in the Surakarta region. The collected data were tested using Kruskal Wallis statistical tests. Result: The results showed that most of the sample (72%) had good knowledge and most of them (54.2%) had regular visits to the dentist. The Kruskal Wallis test shows that there was a correlation between the high knowledge group (p = 0,027) and intermediate knowledge group (p = 0.004) with a regular dental visit frequency. Conclusion: There was a correlation between restorative dentistry treatment knowledge and the frequency of regular visits to dentists in upper-middle-class society. High and Intermediate knowledge about restorative dentistry have a significant correlation with a regular dental visit.